Length-Weight Relationships and Condition Factor of 33 Freshwater Fish Species in the Recently Impounded Soubré Reservoir in Côte d’Ivoire (West Africa) - Tresor, Konan Kouadio Ange; Mathieu, Dietoa Yehe; Leonard, Tah; Sebastino, Da Costa Kouassi (Journal of Fisheries and Environment, 2023)
Catches of artisanal fishers using a variety of fishing gears were analyzed in the recently filled Soubré Reservoir in southwestern Côte d'Ivoire from August 2019 to July 2021. The length-weight relationship (LWR) and condition factor (K) were estimated for the 33 most abundant fish species. To estimate the parameters of these relationships, 8,194 specimens representing 14 families were used. Fish sizes ranged from 5.4 cm SL (8 g body weight) in Brycinus imberi (Peters, 1852) to 107.5 cm SL (14,500 g body weight) in Lates niloticus (Linnaeus, 1758). The allometric coefficient (b) of the LWR showed a range from 2.5 for Mormyrops anguilloides (Linnaeus, 1758) to 3.22 for B. imberi (Peters, 1852), with a mean value of 2.88. The median and modal values of b were 2.91 and 2.64, respectively. The r2 value ranged from 0.87 in Petrocephalus bovei to 0.99 in Heterotis niloticus (Linnaeus, 1758). The condition coefficient (K) ranged from 0.7±0.062 (Hepsetus odoe) to 4.14±0.52 (Coptodon zillii). The highest values of the coefficient K were found for three species of the family Cichlidae. Moreover, the value of K for 28 of the species sampled (84%) in Soubré Reservoir was greater than one (1), indicating the wellbeing of the majority of fishes in this water body. In addition, the study provides the first reference regarding the length–weight relationship for Hydrocynus forskahlii (Cuvier, 1819) living in this region.